Legal aid - right or privilege / R Rajeswaran and Dr. S. Sothirachagan - Rajeswaran, R.; Sothirachagan, S. (Faculty of Administratron and Law, 2001)
Thus, boldly proclaimed the barons of England when they extracted the Magna Carta from King John. It is a commitment that has been made countless number of times, before and since, in virtually every country. Throughout recorded history and in spite of man's inhumanity to man and social inequality, the vow that justice should be made available to all who seek it, irrespective of cost, has been continually echoed. No thinking person of whatever creed or political belief- however narrow or reactionary in outlook - has openly disagreed with this as a basic right of civilized existence.